2019
DOI: 10.1158/0008-5472.can-19-0384
|View full text |Cite
|
Sign up to set email alerts
|

PPARδ Mediates the Effect of Dietary Fat in Promoting Colorectal Cancer Metastasis

Abstract: The nuclear hormone receptor peroxisome proliferatoractivated receptor delta (PPARd) is a ligand-dependent transcription factor involved in fatty acid metabolism, obesity, wound healing, inflammation, and cancer. Although PPARd has been shown to promote intestinal adenoma formation and growth, the molecular mechanisms underlying the contribution of PPARd to colorectal cancer remain unclear. Here, we demonstrate that activation of PPARd induces expansion of colonic cancer stem cells (CSC) and promotes colorecta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…In contrast to the prosenescent effects of PPARβ/δ in endothelial cells, Bernal and colleagues reported that PPARβ/δ maintains the proliferative undifferentiated phenotype of adult neuronal precursor cells, probably through activation of SOX2, one self-renewal regulatory factor [145]. This is in line with the findings from Wang and colleagues showing that colonic cancer stem cell expansion was induced by PPARβ/δ through direct transcriptional activation of Nanog [135].…”
Section: Pparβ/δ and Replicative Immortalitymentioning
confidence: 57%
See 1 more Smart Citation
“…In contrast to the prosenescent effects of PPARβ/δ in endothelial cells, Bernal and colleagues reported that PPARβ/δ maintains the proliferative undifferentiated phenotype of adult neuronal precursor cells, probably through activation of SOX2, one self-renewal regulatory factor [145]. This is in line with the findings from Wang and colleagues showing that colonic cancer stem cell expansion was induced by PPARβ/δ through direct transcriptional activation of Nanog [135].…”
Section: Pparβ/δ and Replicative Immortalitymentioning
confidence: 57%
“…Similar to the exposure to GW501516, a high fat diet induced expression of Nanog, accelerated tumor growth and liver metastasis formation and knockout of PPARβ/δ completely inhibited these effects. This identifies a novel PPARβ/δ-mediated mechanism responsible for the contribution of dietary fat to colorectal cancer initiation and metastasis [135].…”
Section: Pparβ/δ and Invasion And Metastasismentioning
confidence: 97%
“…One possibility is that a single T allele is sufficient to compensate for the oncogenic effects of a copy of the C allele, which would suggest that the CC genotype is a deleterious marker of CRC susceptibility in Chinese populations. Activation of PPARδ induces colonic CSC expansion and drives the metastasis of CRC to the liver by binding to the Nanog promoter and enhancing the expression of this gene, indicating that Nanog may also be a biomarker of CRC liver metastasis [48]. PPARδ-87T>C genotypes may similarly be used as a biomarker to gauge CRC risk.…”
Section: Discussionmentioning
confidence: 99%
“…The precise role of fat-rich diet in inducing CRC is still a matter of debate. In fact, mounting evidences emerging from cellular and animal studies point to a direct role of dietary fats in increasing colonic cell proliferation and tumorigenicity [12,13,15,16,[32][33][34][35]. By contrast, a recently published meta-analysis reported a negative correlation between HFD and CRC risk [36].…”
Section: Correlating Diet Intestinal Homeostasis and Colorectal Cancmentioning
confidence: 99%
“…Exposure to HFD induced expansions of the CSCs pool and promoted the expression of Nanog and CD44v6, which are related respectively to CSCs self-renewal and metastatic ability [188]. In particular, the PPARδ-Nanog axis was responsible for the effect of HFD in accelerating CRC liver metastasis [34]. Further studies are needed to define which dietary components are specifically responsible for activating proliferative and survival pathways in intestinal CSCs.…”
Section: Effect Of Dietary Factors On Iscs and On The Development Of Crcmentioning
confidence: 99%